Resveratrol (3,5,4′-trihydroxystilbene) and its properties in oral diseases - Perrone, Donatella (Exp Ther Med, 2017)
Health promotion strategies and lifestyle changes are important in disease prevention. Oral health has received a large amount of attention previously as it is a fundamental component of general health and it contributes to the quality of life. Therefore, the study of associations between diet, health and the presence of bioactive compounds in food is receiving a substantial amount of attention. In the present review the effects and targets of a natural polyohenolic stilbenoid compound; resveratrol (3,5,4′-trihydroxystilbene; RSV) is assessed, and the future prospects for RSV in promoting oral health are considered. RSV is a phytoalexin, synthesized by a wide range of plants and abundantly extracted in grape skin, it has been purported to exert a multiplicity of anti-inflammatory, anti-viral, anti-microbial, estrogenic, anticancer, cardioprotective, neuroprotective and immunomodulatory functions. In this review, following an introduction documenting the biochemistry of RSV and RSV glucosides, the bioavailability and pharmacokinetics of RSV are described. Considering its multiple properties, the present review has focused on the potential benefits of RSV as an antioxidant and chemopreventive agent.